2019
DOI: 10.3389/fped.2019.00258
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax and Chylous-Like Diseases in Children: Clinical Management

Abstract: Background: Chylothorax and chylous-like diseases are rare conditions and difficult to treat. But they may represent potentially life-threatening disorders and important causes of morbidity and prolonged hospitalization, especially in critically ill children. Conservative as well as surgical therapeutic management strategies are continuously performed at our institution, however the results have never been evaluated and no guidelines for treatment recommendations have been put into practice so far. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…The mean gestational age at diagnosis was 31.7 weeks. Infants constituted the largest group of patients in which the first symptoms of chylothorax were observed (45%) [2][3][4], Additional demographic information is shown in Table 1. Causes of chylothorax are extremely diverse.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean gestational age at diagnosis was 31.7 weeks. Infants constituted the largest group of patients in which the first symptoms of chylothorax were observed (45%) [2][3][4], Additional demographic information is shown in Table 1. Causes of chylothorax are extremely diverse.…”
Section: Resultsmentioning
confidence: 99%
“…However, the analysis of the available literature shows that iatrogenic factors are the most common cause (70.8%). Among surgical procedures contributing to the development of chylothorax, cardiothoracic surgeries are most prevalent, with predominance of Fontan procedures and congenital heart defect corrective surgeries (61.2%) [2], [3], [6]- [30]. A significant group undergoing these procedures were infants with genetic conditions, such as Noonan syndrome, Down syndrome or Gorham disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Resolution of chylothorax has been described with TPN (complete oral intake cessation) [Bond 1993], a fat-free/ low-fat diet [Chan 2010;BĂĽttiker 1999], or an MCT plan [Chan 2010;Biewer 2010;Densupsoontorn 2005;Cormack 2004;Hermon 2019;Chan 2006] in children with variable success rates, but comparisons of the therapeutic effectiveness of nutrition support modalities in children are few and inconsistent. Nguyen et al [1995] reported that in 15 patients on TPN or a low-fat enteral diet, the average duration of lymph leak was 13.7 versus 13.2 days, respectively.…”
Section: Introductionmentioning
confidence: 99%